Processes of Nucleation of Amorphous As-S Films at Condensation on Carbon Substrates - Рђ.V.В Dalekorej; V.P.В Ivanitsky; V.S.В Kovtunenko; Рњ.V.В Stoika (Журнал нано- та електронної фізики)
Initial stages of vacuum condensation of As-S amorphous films on carbon substrates at the stages of nucleation and formation of condensed phase islands are studied using the electron microscopy technique. Two stages of the processes of critical nuclei formation were found: intense primary nucleation and slow secondary nucleation that occurs in parallel with the growth of the formed nuclei. The sizes of the critical nuclei of the amorphous As-S films, the primary nuclei density, the size distribution of the condensed phase islands at the moment of the nucleation processes termination and the mean diffusion length for difВferent atomic particles of the As-S vapor phase on the substrate surface were determined. The results obВtained show that at room condensation temperatures most of various multi atomic particles of the AsnSm vapor have rather high diffusion mobility over the carbon substrate surface. Therefore, when simulating the condensation processes, the As-S materials could be considered as a non-equilibrium two-dimensional gas with an extremely complicated chemical composition.